The effects of shape-setting on transformation temperatures of pseudoelastic shape memory alloy springs - Asl, Farideh Jahanbazi (H. : ĐHQGHN, 2020)
Since shape memory alloy (SMA) wires can hardly ever be reliably employed under compressive loadings, SMA springs are developed as axial actuators with the ability of withstanding both tension and compression. In this paper, shape memory alloy helical springs are produced by shape-setting two types of wires: one with shape memory effect (SME) and the other with pseudoelasticity (PE) at the ambient temperature. Phase transformation temperatures of the produced springs are measured by differential scanning calorimetry (DSC), and the influences of effective parameters including cold work, heat treatment temperature and duration, and cooling rate are investigated on transformation temperatures of the products. The results show that phase transition temperatures of the fabricated springs can be tuned by performing cold work and by adjusting temperature and duration of the conducted heat treatment as well as the subsequent cooling rate. It is found that transformation temperatures of the springs fabricated using the SME wire increase as the heat treatment temperature increases. However, for samples manufactured using PE wire, transformation temperatures first increase and then decrease with the increase in the heat treatment temperature. An increase in the cooling rate leads to a decrease in the austenite final temperature (Af), and an increase in the extent of cold work leads to the increase in transformation temperatures especially Af.